SOCIAL-PHILOSOPHICAL ANALYSIS OF THE PROBLEM OF HUMAN ESSENCE AND THE MEANING OF LIFE IN PHILOSOPHY (World Bulletin of Education and Learning, 2025)
This article analyzes the essence of man, the process of his understanding of the meaning of life, and the socio-philosophical content of these concepts. The role of man in society, spiritual maturity, and the formation of a system of values are considered on the basis of philosophical approaches.
Keywords: Man, life, perfection, goal, eternal, mind, consciousness, will, ability, freedom, thinking, perception, concentration.